1986
DOI: 10.1113/jphysiol.1986.sp016344
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine blockage of basolateral potassium channels in the amphibian urinary bladder.

Abstract: SUMMARY1. Basolateral membranes of the frog urinary bladder were investigated after increasing the cationic conductance of the apical membrane by the incorporation of nystatin.2. K+ currents were recorded in the presence of a mucosa to serosa oriented K+ gradient (SO42-Ringer solution). Nystatin caused a rapid rise of the short-circuit current (Ihe) followed by a slow increase over a period of 1-2 h.3. Impedance analysis showed that the apical membrane resistance was drastically reduced by nystatin. The slow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Such situations could be achieved by permeabilizing the apical membrane with an ionophore [6,21]. This treatment results in the appearance of two semicircles in the Nyquist plot, each of them reflecting the properties of the apical and basolateral membranes.…”
Section: Preparationmentioning
confidence: 99%
“…Such situations could be achieved by permeabilizing the apical membrane with an ionophore [6,21]. This treatment results in the appearance of two semicircles in the Nyquist plot, each of them reflecting the properties of the apical and basolateral membranes.…”
Section: Preparationmentioning
confidence: 99%
“…As shown in Fig. 3, dexamethasone produced a slow increase in 1SC that reached & Erlij, 1988;Van Driessche, 1986) showed that as the apical membrane is progressively shunted by nystatin the impedance data pass first through an intermediate period in which they 1986). For these experiments the apical side of the epithelia was perfused with a solution in which K+ was the major monovalent cation.…”
Section: Apical Membrane Capacitancementioning
confidence: 99%
“…A single time constant is observed in the impedance plots of tight epithelia because CD is much larger than CQ while the apical membrane resistance (Ra) is larger than the basolateral membrane resistance (Rb) (Van Driessche, 1986;Granitzer, Leal, Nagel & Crabbe, 1991a;Wills, Purcell & Clausen, 1992). A particularly important consequence of these relationships is that the measurements of Cm reflect almost exclusively the value of Ca because transepithelial capacitance is related to apical and basolateral capacitance by:…”
Section: Apical Membrane Capacitancementioning
confidence: 99%
“…In experimental studies in rats, either intravenous or intraalveolar lidocaine reduced fluid clearance in rats by 50% (189). Because lidocaine did not inhibit ENaC when expressed in oocytes, it seems that the inhibitory effect on vectorial fluid transport was primarily on the basal surface of alveolar epithelial cells, either through an effect on the activity of Na ϩ -K ϩ -ATPase or through an indirect effect through blockade of potassium channels, a wellknown property of lidocaine (47,156,302,357). The effect of lidocaine was completely reversible with ␤ 2 -agonist therapy (189).…”
Section: Anestheticsmentioning
confidence: 99%